PENGARUH IKLIM ORGANISASI DAN MOTIVASI TERHADAP KEPUASAN KERJA DENGAN CAREER PLATEAU SEBAGAI VARIABEL MEDIASI PADA DINAS PERTANIAN TANAMAN PANGAN DAN PETERNAKAN KABUPATEN PATI (Students' Journal of Economic and Management, 2013)
The purpose of this study was to examine and describe the effect of: 1) organizational climate on Career Plateau, 2) motivation toward career plateau, 3) organizational climate on Job Satisfaction, 4) Motivation to Job Satisfaction, and 5) Career Plateau on Job Satisfaction. This research, carried out with the object of Pegawai Negeri Sipil at the Dinas Pertanian Tanaman Pangan dan Peternakan Kabupaten Pati and a sample of 111 people by using purposive sampling. Data collection distributing questionnaires, using a questionnaire with Likert scale model modification 7 scale and descriptive analysis technique, partial correlation and linear regression at a significance level of 5%. The research results of linear regression line equation model 1 is Y1 = - 0.138 X1 - 0.487 X2. Linear regression line equation model 2 is Y2 = 0.170 X1 + 0.373X2 - 0.255 Y1. Based on the calculation of test data analysis through mediation concluded that career plateau can not mediate (direct effect) on the variables of organizational climate and work motivation on job satisfaction. Keywords: Organizational Climate, Motivation, Career Plateau, and Job Satisfaction.